Pengaruh Model Discovery Learning Dengan Pendekatan STEM Terhadap Hasil Belajar Peserta Didik Kelas VIII SMP Negeri 3 Lubuk Basung - Stefvannof, Diego; Oktavia, Rani; Lestari, Tuti; Prima Sari, Monica; Wati, Fatma (Journal of Comprehensive Science, 2024)
Student learning outcomes are often unsatisfactory due to learning methods that still dominantly use lectures and do not actively involve students. This method tends for making learner passive at studying. For improving this situation and make learning more effective, it so urgent for overhaul the teaching oncoming. One way is for integrate learning models that involve STEM components. The focus through the following discussion the aim is to find out “the effect of the Discovery Learning learning model with a STEM approach on the learning outcomes of grade VIII students at SMPN 3 Lubuk Basung”.This research used a quasi-experimental design by Non-Equivalent Control Group Design. This research population consisted of VIII grade students at SMPN 3 Lubuk Basung for the 2024/2025 academic year. The sample method used was purposive sampling, where one VIII grade was selected being experimental group also the other VIII class being control group. The instruments using this study included multiple choice experiment of 20 questions also a student response questionnaire. Data analysing has been implemented with “normality test, homogeneity test, and non-parametric test, namely Mann-Whitney test”. The survey of learner proves that most of them give positive responses to application of the Discovery Learning model by STEM approach through a ratio 45% of learner agreeing (S) and 52% strongly agreeing (SS). The hypothesis experimental results show significant figures with large 0.000 <0.05, meaning that the application of this model significantly improved student learning outcomes compared to the Discovery Learning model that did not integrate STEM. The N-Gain testing at experimental group reached 0.8594 which is included at high classification. The teaching use with the STEM-based Discovery Learning model was recorded at 97%. This finding shows thats the using Discovery Learning combined by STEM approach found positively and significant effect at learner understanding of introduction to cell material.